2005
DOI: 10.1111/j.1469-8137.2005.01504.x
|View full text |Cite
|
Sign up to set email alerts
|

Nickel hyperaccumulation as an elemental defense of Streptanthus polygaloides (Brassicaceae): influence of herbivore feeding mode

Abstract: Summary• No study of a single nickel (Ni) hyperaccumulator species has investigated the impact of hyperaccumulation on herbivores representing a variety of feeding modes.• Streptanthus polygaloides plants were grown on high-or low-Ni soils and a series of no-choice and choice feeding experiments was conducted using eight arthropod herbivores. Herbivores used were two leaf-chewing folivores (the grasshopper Melanoplus femurrubrum and the lepidopteran Evergestis rimosalis ), a dipteran rhizovore (the cabbage mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 64 publications
(120 reference statements)
2
61
0
1
Order By: Relevance
“…1A-C). Results from the A. pintodasilvae trials provide circumstantial support to the hypothesis that Ni defends this hyperaccumulator species from herbivory in agreement with previous studies on Ni hyperaccumulation Boyd and Jhee, 2005;Boyd and Moar, 1999;Gonçalves et al, 2007;Jhee et al, 2005Jhee et al, , 2006aMartens and Boyd, 1994). However, A. simplex also induced a significant inhibition of food intake and deterred feeding in T. castaneum despite the low concentration of Ni in its leaves (65 ± 26 μg g −1 dry weight).…”
Section: No-choice and Choice Testssupporting
confidence: 89%
“…1A-C). Results from the A. pintodasilvae trials provide circumstantial support to the hypothesis that Ni defends this hyperaccumulator species from herbivory in agreement with previous studies on Ni hyperaccumulation Boyd and Jhee, 2005;Boyd and Moar, 1999;Gonçalves et al, 2007;Jhee et al, 2005Jhee et al, , 2006aMartens and Boyd, 1994). However, A. simplex also induced a significant inhibition of food intake and deterred feeding in T. castaneum despite the low concentration of Ni in its leaves (65 ± 26 μg g −1 dry weight).…”
Section: No-choice and Choice Testssupporting
confidence: 89%
“…These plants, which accumulate up to several percent of heavy metals in the dry mass of their aboveground parts, are called "hyperaccumulators" (Brooks et al, 1977). In their natural habitats, metal-rich soils in many parts of the world, this type of heavy metal accumulation serves as a defense against pathogens and herbivores Martens and Boyd, 1994;Boyd et al, 2002;Hanson et al, 2003;Jhee et al, 2005). They can now be used for the decontamination ("phytoremediation") of anthropogenically heavy metal-contaminated soils and in some cases also for the commercial extraction ("phytomining") of high-value metals (mainly Ni) from metal-rich soils (Baker et al, 1994;McGrath and Zhao, 2003;Chaney et al, 2005).…”
mentioning
confidence: 99%
“…Many studies have shown that metal hyperaccumulation serves as a defense mechanism against herbivores and pathogens [159][160][161][162][163]. Herbivores that were given the choice between Senecio coronatus plants grown on different nickel levels chose those plants which accumulated the lowest amount of metal [161].…”
Section: Biological Function Of Nickel Hyperaccumulationmentioning
confidence: 99%
“…The Ni hyperaccumulator Streptanthus polygaloides was more susceptible to turnip mosaic virus than the related nonaccumulator S. insignis, in particular when Ni-fertilized plants were compared [168]. A very recent study [163] testing the effect of nickel hyperaccumulation in Streptanthus polygaloides on different types of herbivores has shown that hyperaccumulation is an efficient protection against tissue-chewing herbivores, but much less effi cient against herbivores feeding on vascular tissue. This is logical in view of the preferentially epidermal sequestration of the metal in most hyperaccumulators (see Section 4.2).…”
Section: Biological Function Of Nickel Hyperaccumulationmentioning
confidence: 99%